2020
DOI: 10.1101/2020.06.29.20131367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Viasure SARS-CoV-2 RT-qPCR kit (CerTest Biotec) using CDC FDA EUA RT-qPCR kit as a gold standard

Abstract: Abstract. Background. Several RT-qPCR kits are available for SARS-CoV-2 diagnosis, some of them with Emergency Use Authorization (EUA) by FDA, but most of them lacking of proper evaluation studies due to covid19 emergency. Objective. We evaluated Viasure RT-qPCR kit (CerTest Biotec, Spain) for SARS-CoV-2 diagnosis using CDC FDA EUA kit as gold standard. Results. Although we found the lack of RNA quality control probe as the main limitation for Viasure kit, the sensitivity was up to 97.5% and specificit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…It is also reported that the elderly as well as those with underlying health issues such as cancer, chronic respiratory disease, diabetes and cardiovascular disease have a greater chance of developing serious illness [20] , [21] , [22] , [23] , [24] , [25] . In particular, those 80 plus people who have never been vaccinated for pneumonia or flu, who live in facility-based long-term care services and residential care homes, are at greater risk for developing deadly diseases owing to COVID-19 [27] , [28] , [29] , [30] , [31] , [32] . In addition, COVID-19 has been observed to be more lethal in senior citizens with chronic illnesses including kidney lung and heart if they are infected with HIV or have had cancer.…”
Section: Sars-cov-2mentioning
confidence: 99%
See 4 more Smart Citations
“…It is also reported that the elderly as well as those with underlying health issues such as cancer, chronic respiratory disease, diabetes and cardiovascular disease have a greater chance of developing serious illness [20] , [21] , [22] , [23] , [24] , [25] . In particular, those 80 plus people who have never been vaccinated for pneumonia or flu, who live in facility-based long-term care services and residential care homes, are at greater risk for developing deadly diseases owing to COVID-19 [27] , [28] , [29] , [30] , [31] , [32] . In addition, COVID-19 has been observed to be more lethal in senior citizens with chronic illnesses including kidney lung and heart if they are infected with HIV or have had cancer.…”
Section: Sars-cov-2mentioning
confidence: 99%
“…Nearly, 15 percent of them have cough and fever, while 90 percent of people have more than one symptom. It has been urged that anyone over 65 with elevated respiratory symptoms must seek medical advice from the health care professionals [27] , [28] , [29] , [30] , [31] , [32] . As most visitors to old-age homes may be carriers of the viral infection caused by SARS-CoV-2, visitors are not permitted to enter the old-age homes.…”
Section: Sars-cov-2mentioning
confidence: 99%
See 3 more Smart Citations